Exploring the Construction of “Indonesianness” in Mahmud Yunus’s Tafsir Qur’an Karim - M. Dalip; Haris, Abdul Gaffar; Wahyuddin; Azis, Ahmad Ridhai; Mukhlis, Muhammad Mutawalli (Millati: Journal of Islamic Studies and Humanities, 2025)
This article examines Mahmud Yunus’s Tafsir Qur’an Karim in order to explore the meanings of “Indonesianness” embedded in his ways of understanding, interpreting, and contextualizing the Qur’anic text. The study employs a qualitative approach in the form of library research, using Tafsir Qur’an Karim as the primary source and supported by works on Mahmud Yunus’s intellectual biography, Nusantara exegesis, and contextual–humanistic theories of interpretation. Data were collected through systematic identification, classification, and coding of exegetical passages related to the themes of education, poverty, family livelihood, nationalism, social justice, and the management of religious and social diversity. Content analysis is combined with a hermeneutical–contextual reading in order to examine the relationship between the exegetical text, the socio-historical context of early twentieth-century Indonesia, and the contemporary needs of Indonesian society. The findings show that Mahmud Yunus constructs an exegetical approach characterized by social engagement, rationality, and communicative clarity, through which the Qur’an is presented as an ethical–practical guide for the Indonesian socio-national project. This project emphasizes education, diligence, family responsibility, social solidarity, and religious moderation. The study thus affirms the continuing relevance of Mahmud Yunus’s exegetical legacy for strengthening contemporary Indonesian discourses on Islam, nationalism, and social justice.